Clinical exercise science - Scott, Andrew T. 1979-; Gidlow, Christopher (Christopher J.) (Routledge, Taylor & Francis Group, 2016)
Clinical Exercise Science is an introduction to core principles and best practice in exercise science for students and practitioners working with clinical populations. Combining the latest scientific research with evidence-based, practitioner-led analysis, the book offers integrated coverage of the full clinical exercise curriculum, including:Pathophysiology of exercise and disease, Exercise as a clinical intervention, Exercise, nutrition, and lifestyle Health behaviour change, and Clinical skills in exercise science. The book covers a wide range of conditions, including cardiovascular disease, pulmonary disease, metabolic disease and mental health problems, and includes an array of useful features to guide student learning, such as case studies, study tasks, definitions of key terms and suggestions for further reading. With contributions from leading researchers and health practitioners, this is an invaluable foundation text for any clinical exercise science course, and useful reading for any student or practitioner working in exercise science, exercise rehabilitation, health science or physical therapy.